2023
DOI: 10.3354/esr01278
|View full text |Cite
|
Sign up to set email alerts
|

Key issues in assessing threats to sea turtles: knowledge gaps and future directions

MMPB Fuentes,
E McMichael,
CY Kot
et al.

Abstract: Sea turtles are an iconic group of marine megafauna that have been exposed to multiple anthropogenic threats across their different life stages, especially in the past decades. This has resulted in population declines, and consequently many sea turtle populations are now classified as threatened or endangered globally. Although some populations of sea turtles worldwide are showing early signs of recovery, many still face fundamental threats. This is problematic since sea turtles have important ecological roles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 455 publications
0
0
0
Order By: Relevance
“…Despite the concern about conserving and restoring sea turtle populations and their critical habitats in this vital region, the scientific, published literature is still, and most of the scientific knowledge is contained in grey literature (thesis, local conservation and monitoring projects technical reports) (Guzmán-Hernández, 2023). In this regard, this article also contributes to scientifically formalizing long-term knowledge that is used for decision-making in this region on key international conservation issues, threats and research questions (Fuentes et al, 2023;Hamann et al, 2010;Rees et al, 2016;Wildermann et al, 2018). Regarding Kemp's ridley turtles, the coast of Campeche is the historic southern boundary of its annual breeding zone (from April to June in Campeche), and that area also hosts critical feeding grounds for adults (Gradzens & Shaver, 2020;Guzmán-Hernández et al, 2007, 2019.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite the concern about conserving and restoring sea turtle populations and their critical habitats in this vital region, the scientific, published literature is still, and most of the scientific knowledge is contained in grey literature (thesis, local conservation and monitoring projects technical reports) (Guzmán-Hernández, 2023). In this regard, this article also contributes to scientifically formalizing long-term knowledge that is used for decision-making in this region on key international conservation issues, threats and research questions (Fuentes et al, 2023;Hamann et al, 2010;Rees et al, 2016;Wildermann et al, 2018). Regarding Kemp's ridley turtles, the coast of Campeche is the historic southern boundary of its annual breeding zone (from April to June in Campeche), and that area also hosts critical feeding grounds for adults (Gradzens & Shaver, 2020;Guzmán-Hernández et al, 2007, 2019.…”
Section: Discussionmentioning
confidence: 99%
“…This result is consistent with the fact that more than 70% of the fishing fleet in Campeche uses gillnets (Secretaría de Pesca, 2004), in contrast to adjacent waters (like the northern Yucatan Peninsula), where longlines are used mainly by industrial and artisanal fleets (Cuevas et al, 2018;Jiménez-Badillo et al, 2006;Mexicano-Cíntora et al, 2007). The risk of sea turtle bycatch increases when fishing activities are conducted in feeding grounds and migration routes, particularly when the fishing gear is set for many hours without inspection, which is considered a wrong fishing practice (Fuentes et al, 2023;Rees et al, 2016), as has been reported to be the case in Campeche (Cuevas et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fishing is one of the main threats to ecosystems, exerting pressure not only on target species for coastal and oceanic fisheries ( i.e ., overfishing), but also on species with no commercial value ( i.e ., bycatch) ( ICMBIO, 2016 ; Sandoval Gallardo et al, 2021 ; Karnad, 2022 ). The impacts of fishery activity on sea turtles, as with most marine megafauna, are often the accidental capture in gillnets, lines and hooks, and collision with vessels, which results in mortality ( Lewison et al, 2004 ; Fuentes et al, 2023 ). Large regions of the ocean where industrial fisheries overlaps sea turtle distribution have been well understood but it is not the same for small-scale fisheries ( Kroodsma et al, 2018 ; Sequeira et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Conservation can be a means of sharing knowledge or education with the wider community about the importance of turtle conservation to protect turtle habitats in Indonesia so that they do not become extinct (Komarudin, 2023). Land shifts that cause damage to coastal habitats and feeding areas, death of turtles due to fishing activities, inadequate management of conservation techniques, climate change, disease, taking of turtles and their eggs, and the threat of predators are factors causing the decline in turtle populations (Fuentes et al, 2023).…”
Section: Introductionmentioning
confidence: 99%